The Effectiveness of Group Guidance using Prezi Media to Increase Learning Motivation of High School Students - Safitri, Indah; Ridhani, Akhmad R.; Prasetia, Muhammad E. (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: Student motivation plays a crucial role in learning outcomes, and educators are increasingly exploring innovative approaches to enhance it. The integration of digital media, such as Prezi, into guidance services offers new potential in improving student engagement and learning motivation. Objective: This study aims to determine the effectiveness of group guidance using Prezi media to increase student motivation at SMAN 1 Alalak. Method: This research used an experimental design with a one-group pre-test and post-test approach. The study was conducted at SMAN 1 Alalak in 2023 with a sample of 7 students selected through purposive sampling. Data were collected using a learning motivation scale. Result: The results showed that student motivation before the intervention was in the low category with a mean score of 35.14. After receiving group guidance using Prezi media, the motivation score increased significantly to 82.86, falling into the high category. Conclusion: The findings indicate that group guidance using Prezi media is effective in increasing students' learning motivation. Contribution: This research contributes theoretical and practical insights into the implementation of group guidance services using digital media, highlighting its positive impact on enhancing learning motivation among high school students.